Trajectories of Subjective Well-Being: A Growth Mixture Modeling Analysis on Longitudinal Data from Iceland - Íris Anita Eyþórsdóttir. Kuhlman 1994- (2023)
This study aims to analyse whether there are different subgroups in Iceland with varying trajectories of Subjective Well-Being (SWB) over time and to identify potential determinants of subgroup membership. Data from the longitudinal study Health and Well-being from the Icelandic Directorate of Health was analysed for 2.425 adults aged 18 to 80 who participated from 2007 to 2017, a period coinciding with a financial crisis and significant changes in income inequality. The study uses Growth Mixture Modeling to identify distinct subgroups with varying SWB trajectories, and multinomial logistic regression to predict group membership based on determinants. Three groups were identified whose SWB trajectories differ. The Change group (n = 126) showed increasing SWB over time. The Low group (n = 1997) and High group (n = 302) showed no change in SWB and had consistently differing levels of SWB over the 10-year period. Group membership was determined by age, gender, household income, relative deprivation, financial sustainability, relationship status, number of children, and physical health. The findings indicate the presence of three distinct SWB trajectories among the Icelandic population. The study emphasises the importance for policymakers to consider the presence of social gradients in SWB in Iceland, and to develop targeted interventions and policies aimed at improving the quality of life for various subgroups. Markmið þessarar rannsóknar er að skoða hvort hægt sé að bera kennsl á ólíka þróun huglægrar vellíðanar yfir tíma hjá ólíkum hópum á Íslandi, auk þess að kanna hvaða áhrifaþættir spái fyrir um í hvaða undirhóp fólk fellur. Gögn úr langtímarannsókninni Heilsa og líðan Íslendinga frá Embætti landlæknis voru greind fyrir 2.425 einstaklinga á aldrinum 18 til 80 ára sem tóku þátt 2007 til 2017. Á umræddu tímabili átti sér stað bankahrun og miklar breytingar á tekjuójöfnuði. Þroskamynsturslíkön (e. Growth Mixture Modeling) voru notuð til að bera kennsl á ólíka undirhópa og margbreytutvíkosta aðhvarfsgreining (e. ...